RESILIENSI PEREMPUAN JANDA NYEROD YANG PERNAH MULIH DEHA - Ida Ayu Pradnya Paramitha; Luh Kadek Pande Ary Susilawati (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2017)
Marriage in Balinese society is closely related to the existing Wangsa in Bali. According to different marriage of Wangsa in Bali, women’s Wangsa will be dropped to follow her husband’s Wangsa which is known as nyerod. Living a family life can’t be separated from household matters that can lead into the end of marriage that can be caused by divorce or death of the husband. For nyerod widow who return back to her bajang house and accepted by the biological family, the status becomes mulih deha. Individuals who have failed in household, some were able to get through stressful situations, but not a little were difficult to pass it. Individuals who are able to respond in a way that is healthy and productive when facing adversity or trauma called resilience. Based on these explanation, this study aim to know the resilience nyerod widow who have hadmulih deha. This study use qualitative research method with case study approach. Respondents in this study are two persons. The techniques of collecting the data were interviews and observation in two nyerod's widow that already mulih deha. Data analysis techniques through three stages, namely open coding, axial coding and selective coding. The results of this study indicated there were occurs twice pressing conditions, breakdown into eight phases, namely adverse events (nyerod), succumbing, survival, adverse events (loss of a spouse), succumbing, survival, recovery, and thriving. Besides that some of internal factors that can support resilient are motivation and hope, from external factors are children, family and social. Keywords: resilience, widow, nyerod, mulih deha